(untitled) (Terr@ Plural, 2020)
To biologist Peter Turchin, wars were more important than agriculture to cooperation and development between humans TURCHIN, Peter (2016). Ultrasociety. How 10,000 years of war made humans the greatest cooperators on Earth. Chaplin: Beresta Books. 266 p. ISBN 10: 0996139516 - ISBN 13: 9780996139519